The Effect of Genogram Technique on Students’ Career Decision in MAN 2 Kota Makassar - Dewi Hidayati; Ahmad Yasser (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
This study is aimed to (1) describe the implementation of genogram technique in students’ career decision, (2) investigate students’ career decision, and (3) investigate the effect of genogram technique on students’ career decision. This study applied quantitative approach and implemented quasi experimental design as well as Pretest-Posttest Control Group Design to 20 samples. Data collection techniques applied in this research were career decision scale, observation, and interview. This study implemented analytical statistic descriptive non parametric wilcoxon signed ranks test as data analysis technique. This study found that (1) there were low category of genogram technique implementation to affect students’ career decision in MAN 2 Kota Makassar before the treatment, while its high category found after the treatment, (2) students’ career decision in MAN 2 Kota Makassar was raised after genogram technique, and (3) genogram technique can increase students’ career decision in MAN 2 Kota Makassar.